Numerical study of magnetohydrodynamics and thermal radiation on Williamson nanofluid flow over a stretching cylinder with variable thermal conductivity - M. Bilal (Alexandria Engineering Journal, 2018)
The effect of nanofluid and thermal radiation on MHD Williamson fluid over a stretching cylinder in the presence of convective boundary conditions is analyzed. The variable thermal conductivity is considered during the formulation of energy equation. Nonlinear ordinary differential equations are attained by proposing relevant similarity transformations on partial differential equations. These non-dimensional ordinary differential equations are then converted to the system of first order ODEs and solved numerically by shooting method. Results are further compared by using bvp4c, a MATLAB built-in function. The results obtained from MATLAB codes are compared with previously published results of the same nature in limiting case. Numerical results of skin-friction coefficient, local Nusselt and Sherwood numbers are systematized in the form of tables. The effect of prominent parameters on velocity, temperature and concentration is displayed by using graphs. It is observed that velocity profile diminishes for the higher values of Weissenberg number but a reverse relation is noticed for the temperature profile. Keywords: MHD, Williamson nanofluid, Stretching cylinder, Variable thermal conductivity, Thermal radiation